Domestic chicken diversity: Origin, distribution, and adaptation - Lawal, R.A.; Hanotte, Olivier H. (Wiley, 2021)
Chicken is the most numerous among the domesticated livestock species. Across cultures, religions, and societies, chicken is widely accepted with little or no taboo compared to other domestic animals. Its adaptability to diverse environmental conditions and demonstrated potential for breeding improvement provide a unique genetic resource for addressing the challenges of food security in a world impacted by climatic change and human population growth. Recent studies, shedding new knowledge on the chicken genomes, have helped reconstruct its past evolutionary history. Here, we review the literature concerning the origin, dispersion, and adaptation of domestic chicken. We highlight the role of human and natural selection in shaping the diversity of the species and provide a few examples of knowledge gaps that may be the focus of future research.